2020
DOI: 10.26452/ijrps.v11i4.3303
|View full text |Cite
|
Sign up to set email alerts
|

Antiurolithiatic activity of Berberis asiatica by In vitro calcium oxalate crystallization methods

Abstract: The primary objective of this research was to investigate the antiurolithiatic effect of the aqueous Heartwood extract of Berberis asiatica (AEBA) on in vitro crystallization methods. The antiurolithiatic behaviour was carried out in the presence and absence of AEBA at the concentration range of 100-1000 μg/ml by employing crystal nucleation, crystal aggregation, and crystal growth assay methods. Standard drug Cystone was made use of positive control in the concentration range of 100-1000 μg/ml. Inhibition eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has been shown that barberry defends the kidneys from oxidative stress and dissuades calcium oxalate from liquefying. Water extract emerged as the most effective preparation [39].…”
Section: Berberis Vulgaris (Barberry Root Bark)mentioning
confidence: 99%
“…It has been shown that barberry defends the kidneys from oxidative stress and dissuades calcium oxalate from liquefying. Water extract emerged as the most effective preparation [39].…”
Section: Berberis Vulgaris (Barberry Root Bark)mentioning
confidence: 99%